Formulation of quality of Islamic basic education: A study in the integrated Islamic elementary school Al-Uswah Magetan - Bagas Mukti Nasrowi; Yusnia Binti Kholifah (Universitas Ahmad Dahlan, 2021)
The development of science and technology that occurs in the current global era has a considerable impact on the changes in human life. These impacts and challenges can be overcome by qualified human resources. Such condition requires educational institutions to continue to improve the quality of their education in order to create qualified human resources. Likewise in Islamic basic education institutions, as the foundation of secondary and higher education, basic education is also in need to continue to improve its quality in order to be able to play a role in facing global changes. Therefore, careful strategy formulation is needed as an effort to make strategic planning in a directed, effective, and efficient manner in the process of improving the quality of Islamic basic education institutions in the current global era. This study aim to describe the formulation of quality of Islamic basic education in SD IT Al Uswah Magetan. The type of research used is a case study. Data collection techniques are used, namely in-depth interviews, participant observation, and study of documents. Data analysis in this study used an interactive analysis model. Then the results of the research are the strategy formulated is focused on curriculum development, human resource development, infrastructure development, environmental development, and student development.